Soil quality index in some cropping systems in plot 17 of Wanagama forest, Gunungkidul, Yogyakarta, Indonesia - Mustofa, Arif; Utami, Sri Nuryani Hidayah; Purwanto, Benito Heru (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
The Wanagama 1 Forest, owned by Universitas Gadjah Mada  in Playen, is an educational and research forest that is home to different species of trees that are managed and treated differently. Finding the quality index values for different cropping strategies in plot 17 of Wanagama Educational Forest 1 was the aim of this study. The soil quality index was determined using three methods: simple addition, scoring and weighting, and summation. The results show that in plot 17 of the Wanagama forest, the highest soil quality index values were found for ebony species and the lowest soil quality index values were found for mahogany and Eucalyptus species. The results showed that all land uses with different types of forest plants had lower soil quality indices. The stepwise analysis results showed that porosity, organic C, cation exchange capacity (CEC), P availability, K availability, and C biomass influenced the soil quality index. Measuring soil quality can help you learn more about soil properties and how to improve it through effective management.